The Effectiveness of Anti-Bullying Teaching Material Through a Deep Learning Approach Based on Project-Based Learning - Kristiwi Estuningsih; Harmanto; Septina Alrianingrum (JTP - Jurnal Teknologi Pendidikan, 2025)
Bullying remains one of the most serious challenges in Indonesian education, with far-reaching impacts on students' psychological, social, and academic development. Bullying that occurs in schools not only reduces learning motivation but also hinders character formation and the development of human values ​​​​in line with Pancasila. This study aims to describe the effectiveness of "Anti-Bullying" teaching materials developed through a Project-Based Learning (PjBL)-based Deep Learning approach in Pancasila Education in Senior High Schools. This study was conducted in a Senior High School in Surabaya in the 2025/2026 academic year. The population of grade XII students was 300 people. The research subjects consisted of Pancasila Education teachers and students in grades XII-7, with a total of 36 students. Data collection was carried out through observation, in-depth interviews, and documentation, as well as data analysis consisting of data reduction, data presentation, and drawing conclusions. The research findings indicate that the implementation of "Anti-Bullying" teaching materials fosters students' reflective, collaborative, and empathetic awareness towards issues of violence in schools. Through their social campaign project, students not only cognitively understand the concept of anti-bullying but also affectively internalize moral and humanitarian values. Based on the survey results, the forms of bullying experienced by students were physical (10.6%), verbal (38%), social (29%), cyber/social media (9.9%), and others (46.9%). These results indicate that the "Anti-Bullying" teaching material has the potential to be an effective medium for character education, relevant to strengthening the Pancasila Student Profile in the context of the Independent Curriculum.